THE ROLE OF ORGANIZATIONAL COMMITMENT AND ORGANIZATIONAL JUSTICE IN INFLUENCING TURNOVER INTENTION THROUGH JOB SATISFACTION AS ITS MEDIATES VARIABLE - Kurnia Magfuroh; Anik Herminingsih (Dinasti International Journal of Education Management And Social Science, 2021)
This research aims to investigate and analyze further relates to the affect which caused by organizational commitment and organizational justice to turnover intention through job satisfaction as its mediator on the employees of PT. Bank XYZ at Regional Office in Jakarta BSD. The criteria of research sample used was permanent employees. The sampling method done by proportional stratified random sampling with a total samples of 154. The data collection technique used a questionnaire. Data analysis method used SEM-PLS. The results showed that the organizational commitment had a positive and significant impact on job satisfaction, but had a negative and significant impact on turnover intention. Organizational justice had a negative and significant impact on turnover intention variables, but had a positive and significant impact on job satisfaction. Job satisfaction had a negative and significant impact on turnover intention. Moreover, job satisfaction in its influence on organizational commitment variable towards turnover intention only resulted on partially mediate and job satisfaction in its influence on the organizational justice variable towards turnover intention also only resulted in partially mediate.